Effects of Pharmacogenetics on the Pharmacokinetics and Pharmacodynamics of Tamoxifen - de Vries Schultink, Aurelia H. M.; Zwart, Wilbert; Linn, Sabine C.; Beijnen, Jos H.; Huitema, Alwin D. R. (Clinical pharmacokinetics, 2015)
The antiestrogenic drug tamoxifen is widely used in the treatment of estrogen receptor-α-positive breast cancer and substantially decreases recurrence and mortality rates. However, high interindividual variability in response is observed, calling for a personalized approach to tamoxifen treatment. Tamoxifen is bioactivated by cytochrome P450 (CYP) enzymes such as CYP2B6, CYP2C9, CYP2C19, CYP2D6 and CYP3A4/5, resulting in the formation of active metabolites, including 4-hydroxy-tamoxifen and endoxifen. Therefore, polymorphisms in the genes encoding these enzymes are proposed to influence tamoxifen and active tamoxifen metabolites in the serum and consequently affect patient response rates. To tailor tamoxifen treatment, multiple studies have been performed to clarify the influence of polymorphisms on its pharmacokinetics and pharmacodynamics. Nevertheless, personalized treatment of tamoxifen based on genotyping has not yet met consensus. This article critically reviews the published data on the effect of various genetic polymorphisms on the pharmacokinetics and pharmacodynamics of tamoxifen, and reviews the clinical implications of its findings. For each CYP enzyme, the influence of polymorphisms on pharmacokinetic and pharmacodynamic outcome measures is described throughout this review. No clear effects on pharmacokinetics and pharmacodynamics were seen for various polymorphisms in the CYP encoding genes CYP2B6 , CYP2C9 , CYP2C19 and CYP3A4/5 . For CYP2D6 , there was a clear gene-exposure effect that was able to partially explain the interindividual variability in plasma concentrations of the pharmacologically most active metabolite endoxifen; however, a clear exposure-response effect remained controversial. These controversial findings and the partial contribution of genotype in explaining interindividual variability in plasma concentrations of, in particular, endoxifen, imply that tailored tamoxifen treatment may not be fully realized through pharmacogenetics of metabolizing enzymes alone.